2022
DOI: 10.3390/su14031702
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Education for Sustainable Development in Engineering Study Programs: A Case of AI Ecosystem Creation

Abstract: The issue of sustainability in education has never been more important for the future of our environment, and strategies to develop the skills needed by younger generations to meet this significant global challenge should be developed across all curricula. There is much focus on the topic of sustainability in business, finance, climate, health, water and education; however, there are some challenges when sustainability needs to be integrated into engineering or fundamental study programs (SPs). In the latter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Researchers in this cluster are positing efforts to understand how digital transformation is shaping society and how engineering education should adapt to it, such as guaranteeing competencies related to sustainability, data science, and others connected to the rise of Industry 4.0 (Gürdür Broo et al, 2022; Okoroafor et al, 2022). In addition, another aspect covered in this cluster is related to the need to integrate SD issues into the curricula of information technology and AI engineering programmes (Paulauskaite‐Taraseviciene et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers in this cluster are positing efforts to understand how digital transformation is shaping society and how engineering education should adapt to it, such as guaranteeing competencies related to sustainability, data science, and others connected to the rise of Industry 4.0 (Gürdür Broo et al, 2022; Okoroafor et al, 2022). In addition, another aspect covered in this cluster is related to the need to integrate SD issues into the curricula of information technology and AI engineering programmes (Paulauskaite‐Taraseviciene et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Education for Sustainable Development (ESD) or Education for Sustainability (EfS) is a vehicle needed by community members to act in the form of contributing to a sustainable lifestyle and to overcome today's global challenges, including climate change, environmental degradation, consumerism, and so forth (Bascopé et al 2019;Glavič 2020;Paulauskaite-Taraseviciene et al 2022). One way to understand learning in the context of ESD is through the development of action competence (Chen and Liu 2020;Sass et al 2020Sass et al , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Xue, Met al's study of the relationship between AI applications and the structure of the corporate workforce found that AI applications in universities are positively correlated with overall employment, which also suggests that teaching and society are interconnected and mutually influential and that this relationship is complex and dynamic [9]. Paulauskaite-Taraseviciene, A et al argued that AI is a sustainable means of education and that colleges and universities can try to utilize a variety of intelligent resources and environments to improve teaching quality and efficiency [10].…”
Section: Introductionmentioning
confidence: 99%